The Influence of Health Education and Prevention of Complications Program Using Wa Group on the Attitudes of Pregnant Women in the III Trimester in Preparing for Birth in the District Kuala Samboja In 2023 - Siahani Laila; Novi Pasiriani; Faridah Hariyani (International Journal of Scientific Multidisciplinary Research, 2023)
AKI in Indonesia is still high, mainly due to direct causes such as hemorrhage, infection, eclampsia, and others. Preparation for childbirth through P4K is necessary, but in practice, many mothers are not adequately prepared to face childbirth, thus requiring education, including through WhatsApp (WA) groups. To analyze the influence of health education from the Maternity Planning and Complications Prevention Program (P4K) using WhatsApp groups on the attitudes of third-trimester pregnant mothers regarding childbirth preparation in Kuala Samboja Village in the year 2023. This study employed a quasi-experimental design with a nonequivalent control group design. The research population consisted of 82 third-trimester pregnant mothers in Kuala Samboja Village from January to March 2023. The sampling technique used the estimation formula, resulting in a sample size of 20 participants. The measurement instruments utilized were the SAP (Scale of Attitude towards Pregnancy) and a questionnaire. Data analysis was performed using the Mann-Whitney test. The description of attitudes among third-trimester pregnant mothers before the intervention in the treatment group had a mean value of 37.10, and after the intervention, the mean value was 64.60. The description of attitudes among third-trimester pregnant mothers before the intervention in the control group had a mean value of 36.00, and after the intervention, the mean value was 53.65. There is a significant difference in attitudes among third-trimester pregnant mothers between the WA Group and the leaflet group in preparing for childbirth, with a significant p-value of 0.000. Education using WhatsApp (WA) Groups is more effective compared to leaflets because the social media platform WA is easier to use and enhances mothers' attitudes towards childbirth preparation